Developing a virtual engineering management community. (3rd March 2016) - Hewitt, Bill; Kidd, Moray; Smith, Robin; Wearne, Stephen
Abstract : The paper reviews the lessons of planning and running an Engineering Management practitioner development programme in a partnership between BP and the University of Manchester. This distance-learning programme is for professional engineers in mid-career experienced in the engineering and support activities for delivering safe, compliant and reliable projects and operations worldwide. The programme concentrates on the why and how of leadership and judgement in managing the engineering of large and small projects and operational support. Two intensive residential weeks are combined with a virtual learning environment over one year. Assessed assignments between and after the residential weeks provide opportunities for individual reflective learning for each delegate through applying concepts and the lessons of case studies to their experience, current challenges and expected responsibilities. This successful partnership between a major global company and a university rich in research and teaching required a significant dedication of intellectual and leadership effort by all concerned. The rewards for both parties and most importantly for the engineers themselves are extensive.